Interpretasi Fase Awan dengan Metode CCO Dan RGB pada Data Satelit Himawari-9 di DKI Jakarta (Studi Kasus: 1 Januari 2023) - Giananti, Attiya Shakila; Darmawan, Yahya; Mulya, Aditya (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
Indonesia is the largest archipelagic country in the world so it receives large amounts of energy from solar radiation which makes it the most active convective region in the world. In December and January, DKI Jakarta tends to experience the rainy season. On January 1 2023, BMKG gave an early warning that it would rain in Jakarta. Reporting from several news reports, in the new year 2023, Jakarta was hit by heavy rain. Cloud phase analysis is needed to determine the potential for rain. This research identifies cloud phases using Himawari-9 satellite image data which is then processed using the Cloud Convective Overlays (CCO) method and the Red Green Blue (RGB) method. The CCO method can identify the distribution of cumulonimbus clouds and the RGB method can determine the flow of air masses, the type of air mass (Airmass), identify cloud phase, and the presence of high clouds containing ice (Day Convective Storm, Day Natural Color, and Cloud Phase Distinction ). The data used are bands 3 (0.6 µm), 5 (1.6 µm), 7 (3.7 µm), 8 (6.2 µm), 10 (7.3 µm), 12 (9.6 µm), 13 (10 .4 µm), and 15 (12.4 µm) at 7.00, 8.00, 9.00, 10.00, 11.00, 12.00, 13.00, and 14.00 WIB (GMT+7). The data was processed and visualized using Grid Analysis and Display System (GrADS) and GMSLPD SATAID software.